2015
DOI: 10.14411/eje.2015.098
|View full text |Cite
|
Sign up to set email alerts
|

Natural breakage of the very long intromittent organ of the seed bug Lygaeus simulans (Heteroptera: Lygaeidae)

Abstract: Abstract. The male intromittent organ of the seed bug Lygaeus simulans ends in a long, sclerotized structure which is used to transfer sperm during mating. Observations suggest that this structure becomes brittle and is liable to breakage after being artificially exposed to the air for an extended period of time. In this study we investigate the frequency of intromittent organ breakage in L. simulans. We first examined the intromittent organ of a sample of males that mated once, and found that breakage was rar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Therefore, the flagellum tip is always exposed to the danger of breakage. Dougherty and Shuler ( 27 ) previously revealed such natural breakage of the flagellum-like intromittent organ in a seed bug species, Lygaeus simulans (Heteroptera: Lygaeidae), and showed that the fractures occurred mainly at the tip. In addition to the difference in material stiffness, the initially curved, softer tip would reduce the probability of being crushed between the flagellum tip and the spermathecal duct wall.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, the flagellum tip is always exposed to the danger of breakage. Dougherty and Shuler ( 27 ) previously revealed such natural breakage of the flagellum-like intromittent organ in a seed bug species, Lygaeus simulans (Heteroptera: Lygaeidae), and showed that the fractures occurred mainly at the tip. In addition to the difference in material stiffness, the initially curved, softer tip would reduce the probability of being crushed between the flagellum tip and the spermathecal duct wall.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the elongated part of the intromittent organ seems to be very fragile [in an extreme case, its diameter is less than 2 μm ( 24 )]. Nevertheless, breakage of the elongated structures does not often occur [0.8 to 3.4% of males of different earwig species ( 26 ), 1.0% of single-mated seed bug males, 22.5% of multiple-mated seed bug males ( 27 ), and 4.5% of field-collected females of a leaf beetle species had within a broken piece of the male intromittent organ ( 24 )]. How do these animals achieve their challenging task without breaking their thin and seemingly fragile structures?…”
Section: Introductionmentioning
confidence: 99%